The Misuse or Abuse of Continuing Powers of Attorney: What Are Appropriate Safeguards?. (29th July 2021) - Stelma-Roorda, Rieneke
Abstract: With a continuing power of attorney adults may provide for a future period of incapacity. The misuse or abuse of CPAs is a growing concern in many countries, increasingly the question is asked whether CPAs should not be furnished with more safeguards. Article 12(4) UNCRPD requires states to ensure appropriate and effective safeguards are in place to prevent abuse. This article focuses on the question what appropriate safeguards preventing the misuse and abuse of CPAs are. The article starts with an overview of the research on the risk of misuse and abuse that to date has been conducted. This information is subsequently used to operationalise the three categories of safeguards mentioned in article 12(4) UNCRPD, providing directions as to how appropriate safeguards might look like. Based on these directions, the safeguards implemented in five European countries have been studied with a view to providing insight into how these countries have tried to meet the requirement to ensure appropriate safeguards are in place. It is concluded that more can be done to ensure adults who want to be involved in the running of their affairs are given the opportunity to do so. In addition, attorneys should be made aware of their rights and responsibilities upon entry into force of the CPA and provided with the necessary support.